AKUNTABILITAS PENGELOLAAN ANGGARAN PEMBANGUNGAN DESA (Studi Kasus Pada Desa Saruran Kabupaten Enrekang) - Idrawahyuni, Idrawahyuni (JSAP : Journal Syariah and Accounting Public, 2020)
This study aims to determine how Accountability Management of Village Development Budget in Saruran Village, Enrekang Regency. This research was conducted at the Saruran Village Office using analysis of effectiveness ratios and efficiency ratios. This type of research is quantitative descriptive. Where data collection used is interview and documentation techniques. The data processed in this study is the report of the Realization of the Village Development Budget in Saruran Village, Enrekang Regency. Data Analysis Techniques used are the Effectiveness Ratio and Efficiency Ratio. The results showed that the efficiency can be said to be very efficient because it produces a ratio level of less than 60%. This means that the Saruran Village Government of Enrekang Regency has been able to realize revenue and budget receipts well.